2011
DOI: 10.1186/1475-2891-10-83
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed intake and blood pressure levels in healthy pre-school Japanese children

Abstract: BackgroundFew studies have examined whether dietary factors might affect blood pressure in children. We purposed to investigate whether seaweed intake is associated with blood pressure level among Japanese preschool children.MethodsThe design of the study was cross-sectional and it was conducted in autumn 2006. Subjects were healthy preschoolers aged 3-6 years in Aichi, Japan. Blood pressure and pulse were measured once by an automated sphygmomanometer, which uses oscillometric methods. Dietary data, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Both healthy Japanese preschoolers and hypertensive Japanese patients with higher seaweed intake had lower blood pressure (Wada et al, 2011). In addition, Lim et al found Laminaria japonica could improve postprandial plasma glucose and lipids profiles in hyperlipidaemic adults (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Both healthy Japanese preschoolers and hypertensive Japanese patients with higher seaweed intake had lower blood pressure (Wada et al, 2011). In addition, Lim et al found Laminaria japonica could improve postprandial plasma glucose and lipids profiles in hyperlipidaemic adults (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…cell cycle assay 24,48, and 72 hours. The cells were harvested by centrifugation at 1,500 rpm for 5 minutes and washed with phosphate-buffered saline.…”
Section: Annexin V-fluorescein Isothiocyanate Assaymentioning
confidence: 99%
“…14 As mentioned in previous reports, 15 seaweed is a subgroup of macroalgae and an available food source in many countries, traditionally those in south-east Asia. 16 Seaweed contains a number of potentially biologically active ingredients, including polysaccharides, proteins, lipids, vitamins, soluble fiber, and minerals, with multiple medical applications in cancer, 17 inflammation, 18 allergy, 19 diabetes, 20 thrombosis, 21 and obesity (by bringing down the caloric value of the diet), 22 and may be useful in the reduction of lipid absorption and risk of cardiovascular disease, 23 hypertension, 24 and other degenerative diseases. 25 These biomedical applications of seaweed are mainly due to its functional groups, which act as capping agents in a green single-step process.…”
mentioning
confidence: 99%
“…Numerous studies are being carried out globally in order to check the bioactivities, such as antibacterial, antiviral, antineoplastic, anti-inflammatory, cytotoxic and antimitotic activities of marine algae or to isolate compounds for different purposes such as pharmaceutical, cosmetics and food preservatives, antifouling coatings, etc. (Fenical and Paul 1984;Hodgson 1984;Scheuer 1990;Ballesteros et al 1992;Sastry and Rao 1994;Armstrong et al 2000;Gonzalez del Val et al 2001;Bhosale et al 2002;Ozdemir et al 2006;Salvador et al 2007;Tierney et al 2010;Wada et al 2011;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%